Psicologia e relações raciais: análise do processo histórico de formação de profissionais da psicologia - Assis, Beatriz Vieira de (Universidade Federal de São Carlos, 2024)
This research aims to analyze Psychology training from the perspective of racial relations in Brazil. To this end, Psychology is articulated as a scientific and educational field that relates to the modes of development and the constitution of subjectivity within culture and social relations. As a basic principle, the racism experienced by Black people is considered, as it structurally organizes Brazilian society and, given this, it is essential that the Psychology course is capable of training professionals who are duly qualified to act competently in the face of racial dynamics. To this end, as a methodology, a theoretical qualitative research approach was conducted on ethnic-racial relations in Psychology training, based on the understanding and explanation of social dynamics. As results, it was possible to perceive that although there have been advances throughout the history of Psychology regarding ethnic-racial issues, it must be recognized that intellectual production under the premise of ethnic and racial relations is still rendered invisible. This context indicates that confronting structural and epistemic racism in the academic field remains a challenge, but that the delineation of the field has been seeded, especially with the enrichment of knowledge promoted by the contribution of Black intellectuals in the authorship of scientific productions.
Psychology and race relations: analysis of the historical process of training psychology professionals
Keywords: Educação superior; Psicologia; Relações étnico-raciais; University degree; Psychology; Ethnic-racial relations; CIENCIAS HUMANAS::EDUCACAO; CIENCIAS HUMANAS::PSICOLOGIA